Nutrition-Sensitive Water Supply, Sanitation, and Hygiene - World Bank (World Bank, Washington, DC, 2019)
This document summarizes evidence and guidance on project design and results framework indicators for nutrition-sensitive water supply, sanitation, and hygiene (WASH) operations and WASH components of other sector and subsector projects. The current body of evidence on the links between WASH and nutrition provides important clues as to what nutrition sensitive enhancements are needed to achieve greater impacts on early child nutrition and human capital. Six principles are outlined that aim to address some of the limitations that are found with conventional WASH interventions. A set of results framework indicators are proposed to support nutrition-sensitive WASH monitoring and evaluation in water supply and sanitation lending operations and for WASH components of projects in other sectors.